2020
DOI: 10.1186/s13020-020-00415-w
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of Indigo Naturalis on acute lung injury induced by influenza A virus

Abstract: Background Infections induced by influenza viruses, as well as coronavirus disease 19 (COVID-19) pandemic induced by severe acute respiratory coronavirus 2 (SARS-CoV-2) led to acute lung injury (ALI) and multi organ failure, during which traditional Chinese medicine (TCM) played an important role in treatment of the pandemic. The study aimed to investigate the effect of Indigo Naturalis on ALI induced by influenza A virus (IAV) in mice. Method The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…In addition, PFWE decreased the gene expression and protein production of inflammatory cytokine (IL-6) and chemokine (CCL2/MCP-1). Although this is the first study to show the efficacy of PFWE in controlling ARDS, similar results have been reported by applying other TCM, such as Indigo naturalis , Huang Qin, or Sophorae flavescentis Radix [ 21 23 ]. Our data further support the use of TCM for the treatment of pulmonary diseases in the acute phase.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, PFWE decreased the gene expression and protein production of inflammatory cytokine (IL-6) and chemokine (CCL2/MCP-1). Although this is the first study to show the efficacy of PFWE in controlling ARDS, similar results have been reported by applying other TCM, such as Indigo naturalis , Huang Qin, or Sophorae flavescentis Radix [ 21 23 ]. Our data further support the use of TCM for the treatment of pulmonary diseases in the acute phase.…”
Section: Discussionsupporting
confidence: 79%
“…In situ dyeing not only simplifies the dyeing process, but also does not require reducing agents, such as sodium hydrosulfite, which is necessary for traditional textile dyeing [70] . The dyed wool textiles displayed visually more uniform colors than other reports of in situ dyeing (Figure S6) [5,9,29] . Additionally, the dyed color did not fade from the wool textiles after washing with water three times.…”
Section: Resultsmentioning
confidence: 93%
“…Indigo is also the basic backbone of many food colorants, such as indigo carmine, a synthetic indigo derivative that is also used as a colorant in daily consumed foods, including fruit juices, tomato ketchup, bread, and dairy. [2,3] Indigo also has antibacterial, anti-inflammatory, and anticancer effects; [4][5][6][7] for example, it is the main active component of isatidis, which can effectively treat influenza. In recent years, indigoids have been recognized as promising functional and biodegradable nanomaterials for preparing "green electronics".…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, oral drug administration exacerbates the metabolic burden in the liver, which might result in metabolic disturbances and thereby increasing the susceptibility to carcinogenesis [ 86 ]. Issues regarding hepatotoxicity have been resolved by the promoted liver regeneration by BT [ 87 ], PP [ 88 ], BD [ 89 ], CH [ 90 , 91 ], LC [ 92 , 93 ], SK [ 94 ], and CWT [ 95 ]. ③ IBD patients are susceptible to malnutrition including anemia, amino acid, and vitamin deficiency [ 96 ], which could be rescued by PP [ 97 ] due to its hematopoiesis-promoting effect [ 98 100 ] and by the addition of pearl that is produced from shellfish mollusks which contain 20 amino acids and Fe and Mg elements [ 101 ].…”
Section: Discussionmentioning
confidence: 99%